Novel Endoscopic Polypectomy Surveillance Technique for Fundic Gland Polyps in Familial Adenomatous Polyposis Can Improve Early Detection of Dysplasia and Gastric Cancer. (18th August 2022) - Wang, Kelly K.; Kim, Katherine; Bancila, Liliana; Lew, Daniel; Larson, Brent K.; Kim, Sungjin; Lee, Jong Y.; Gaddam, Srinivas; Lo, Simon K.
Abstract : INTRODUCTION: Fundic gland polyps (FGPs) are commonly found in patients with familial adenomatous polyposis (FAP) and are considered benign. Biopsies are not routinely performed, and conventional forceps may be time-consuming and/or yield nonrepresentative histology. The purpose of this study was to evaluate the role of a novel endoscopic polypectomy surveillance (EPS), a large volume cold-snare polypectomy technique of random FGPs, in the incidence of dysplasia and gastric cancer (GC) in FAP. METHODS: This is a retrospective longitudinal cohort of patients with FAP referred to a tertiary care center for duodenal adenoma surveillance and who underwent EPS of FGPs between 2001 and 2019. Demographic, endoscopic, and clinicopathologic information was reviewed. RESULTS: Thirty-five patients with FAP were identified at initial endoscopy by the mean age of 43.4 years (±12.8). One hundred thirteen surveillance endoscopies were performed in total using EPS. Dysplasia of FGPs was present on initial esophagogastroduodenoscopy in 7 patients (20%), and 13 additional patients (46.4%) progressed to low-grade dysplasia. Three patients (15%) who subsequently had progression to GC were found to have signet ring cell cancer within the foci of FGPs through EPS. One patient presented as metastatic GC. Progression from nondysplastic FGP to low-grade dysplasia occurred over 63 months (±46.3) with further progression to GC over 34 months (±8.5). Endoscopic risk factors for cancer were polyps >10 mm in size ( P < 0.001) and carpeting of polyps ( P < 0.001). The 5-year cumulative incidence of developing dysplasia was 35.7%. DISCUSSION: We identified that the incidence of dysplasia and GC is higher than previously reported in patients with FAP. Our study used a novel EPS technique and was able to identify GC within the foci of FGPs. Upper endoscopic guidelines should include a more rigorous sampling method for FGPs, such as EPS, to optimize early detection of dysplasia and GC.